Prevalence, Prevention and Management of Bronchopulmonary Dysplasia - Gilfillan MA; Mejia MJ; Bhandari V (Dove Medical Press, 2024)
Margaret A Gilfillan,1 Michelle J Mejia,1 Vineet Bhandari2 1Department of Pediatrics, St. Christopher's Hospital for Children/Drexel University College of Medicine, Philadelphia, PA, USA; 2Department of Pediatrics, The Children's Regional Hospital at Cooper/Cooper Medical School of Rowan University, Camden, NJ, USACorrespondence: Vineet Bhandari, Division of Neonatology, The Children's Regional Hospital at Cooper, One Cooper Plaza, Camden, NJ, 08103, USA, Tel +1-856-342-2000 Extn 1006156, Fax +1-856-342-8007, Email bhandari-vineet@cooperhealth.eduAbstract: Bronchopulmonary dysplasia (BPD) is a complex pulmonary condition that arises in preterm infants secondary to a constellation of adverse exposures contributing to impaired lung development and repair. In many developed countries, the incidence of BPD continues to rise despite the increasing use of evidence-based therapies and efforts to minimize adverse post-natal exposures. Refinement of perinatal care practices that reduce mortality in the most immature infants is likely contributing to this trend; however, a growing population of survivors with respiratory morbidity significantly burdens individuals and health-care systems. Racial and socioeconomic disparities also result in unequal distribution of morbidity within society. In this review, we will outline trends in the incidence of BPD over the last decade and review important risk factors for adverse pulmonary outcomes. The consequences of BPD for long-term health will be described, followed by a comprehensive summary of evidence-based therapies and potential future treatments that can be applied to reduce the incidence, and the prevalence of BPD.Keywords: chronic lung disease, prematurity, invasive mechanical ventilation, non-invasive respiratory support, surfactant, steroids, oxygen, inflammation